Early‐Life Famine Exposure and Risk of Cardiovascular Diseases in Later Life: Findings From the REACTION Study. Issue 7 (9th April 2020) - Du, Rui; Zheng, Ruizhi; Xu, Yu; Zhu, Yuanyue; Yu, Xuefeng; Li, Mian; Tang, Xulei; Hu, Ruying; Su, Qing; Wang, Tiange; Zhao, Zhiyun; Xu, Min; et al.
Abstract : Background: Previous studies reported that early‐life exposure to undernutrition is associated with the risk of diabetes mellitus and metabolic syndrome in adulthood, but the association with risk of cardiovascular disease (CVD) later in life remains unclear. The current study aimed to investigate whether exposure to Chinese famine in early life is associated with risk of CVD. Methods and Results: We used data from REACTION (Risk Evaluation of Cancers in Chinese Diabetic Individuals: A Longitudinal Study), which recruited a total of 259 657 community‐dwelling adults aged 40 years or older from 25 centers across mainland China between 2011 and 2012. Compared with the nonexposed participants, those who had been exposed to famine in early life had a significantly increased risk of total CVD, myocardial infarction, stroke, and coronary heart disease. In the multivariable‐adjusted logistic regression model, the odds ratios (95% CI) for total CVD, myocardial infarction, stroke, and coronary heart disease in fetal famine exposure were 1.35 (1.20–1.52), 1.59 (1.08–2.35), 1.40 (1.11–1.78), and 1.44 (1.26–1.65), respectively; those odds ratios in childhood famine exposure were 1.59 (1.40–1.81), 2.20 (1.52–3.20), 1.82 (1.45–2.28), and 1.80 (1.56–2.09), respectively; and those in adolescent famine exposure were 1.52 (1.27–1.81), 2.07 (1.28–3.35), 1.92 (1.42–2.58), and 1.83 (1.50–2.24), respectively. The main finding of our study is that, compared with those who lived in the less severely affected famine area, individuals in the severely affected famine area had significantly increased risk of total CVD in all 3 exposed groups. Conclusions: Early‐life exposure to undernutrition is associated with significantly increased risk of CVD in later life, especially among those who were in the severely affected famine area.